Empowerment of patients in online discussions about medicine use - van Berkel, Jasper J (BMC Med Inform Decis Mak, 2015)
BACKGROUND: Patient empowerment is crucial in the successful self-management of people with chronic diseases. In this study, we investigated whether discussions about medicine use taking place on online message boards contribute to patient empowerment and could subsequently result in the more effective use of medicines. We discuss the extent to which patient empowerment processes occur in discussions on online message boards, focusing on patients with three disorders with different characteristics: diabetes, Amyotrophic Lateral Sclerosis (ALS) and Attention Deficit / Hyperactivity Disorder (ADHD). Because information is an important factor in both patient empowerment and self-management, we also evaluate the quality of the information being exchanged. METHODS: We used a deductive thematic analysis method based on pre-existing categories. We gathered and analysed 5532 posts related to the conditions ADHD, ALS and diabetes from seven message boards (three for ADHD, three for diabetes, and one for ALS). We coded the posts for empowerment processes and the quality of the information exchanged. RESULTS: We identified patient empowerment processes in posts related to all three disorders. There is some variation in the frequency of these processes, but they show a similar order in the results: patients used the online message boards to exchange information, share personal experiences and for empathy or support. The type of information shared in these processes could contribute to the patient’s self-efficacy when it comes to medicine use. The exchanged information was either correct or largely harmless. We also observed a tendency whereby participants correct previously posted incorrect information, and refer people to a healthcare professional following a request for medical advice, e.g. concerning the choice of medicines or dosage. CONCLUSIONS: Our findings show that patient empowerment processes occur in posts related to all three disorders. The type of information shared in these processes can contribute to the patient’s self-efficacy when it comes to medicine use. The tendency to refer people to a healthcare professional shows that patients still reserve an important role for healthcare professionals in the care process, despite the development towards more self-management. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12911-015-0146-6) contains supplementary material, which is available to authorized users.